Integrasi bahasa melalui podcast content kreator di Youtube - Julianti, Delia; Ratnawati, Ratnawati; Wahyudin, Hilda Aulia; Rozak, Sayyid Abdul (Jurnal IKADBUDI, 2024)
This research aims to: (1) describe the form of language integration of content creators on YouTube; And (2) describe the factors that cause language integration. The method used in This research is qualitative with data collection techniques in the form of involvement-free viewing techniques proficient and note-taking technique. Data analysis is done by classifying the data obtained from some content on YouTube. The factors that influence integration are: Characteristic conditions of language systems/rules; The more similar one to another, the better faster integration; The urgency of absorption of language elements. The more important the element of language in the use of the recipient’s language, the more often it is used, the faster it will be integrate; Language attitude of speakers of the receiving language. Where there is loyalty, pride, and awareness of language norms, if this language attitude decreases, it will increase